2014
DOI: 10.1097/yco.0000000000000024
|View full text |Cite
|
Sign up to set email alerts
|

Melancholia

Abstract: Findings from both studies challenge the view that atypical depression is an entity and the current model of its constituent features. Both found support for primacy of personality style (rather than mood reactivity) and for certain expressions of anxiety. Both effectively argue for and assist shaping of a revisionist model for conceptualizing atypical depression as a syndrome or spectrum disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In the current study, our definition of the AD symptom group was consistent with research that suggested mood reactivity was a poor indicator of AD (6, 7, 17, 20, 21);reversed-vegetative symptoms (and leaden paralysis) could validly be used to identify the AD subtype (28, 30), and a body of research indicating rejection sensitivity should be considered the core feature of AD (6, 17, 22, 23). However, it is quite important to note that the results of the current study do not reflect the findings of depressed individuals who meet the DSM-IV criteria for AD.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In the current study, our definition of the AD symptom group was consistent with research that suggested mood reactivity was a poor indicator of AD (6, 7, 17, 20, 21);reversed-vegetative symptoms (and leaden paralysis) could validly be used to identify the AD subtype (28, 30), and a body of research indicating rejection sensitivity should be considered the core feature of AD (6, 17, 22, 23). However, it is quite important to note that the results of the current study do not reflect the findings of depressed individuals who meet the DSM-IV criteria for AD.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, there is a body of research arguing against mood reactivity as a criterion for AD (6, 7, 17, 20, 21). Specifically, researchers have argued that mood reactivity does not correlate with the other symptoms of AD, is indicative of lower levels of depression, and is a poor indicator of AD (6, 20, 21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we do not claim that a dyshomeostasis-induced sense of low self-efficacy represents a single cause for the entire depression spectrum. Instead, we propose that it may play a particularly important role in melancholia, a subtype of depression with pronounced somatic symptoms and endocrine disturbances (Parker and Paterson, 2014) that differs physiologically from other forms of depression with respect to functional connectivity of visceromotor areas, including SGC and ACC (Guo et al, 2016). Indeed, model-based indices of individual interoception and allostatic control may provide a foundation for differential diagnosis and prognosis, a theme we return to below.…”
Section: A Hierarchical Bayesian View On Fatigue and Depression As Mementioning
confidence: 99%
“…A promising attempt has been made currently to determine the nosological status and diagnostic strategies to melancholia (Parker and Paterson, 2014). Furthermore several biological markers have been suggested to identify this putative endophenotype.…”
Section: Introductionmentioning
confidence: 99%